2015
DOI: 10.1039/c5ra10999j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable wet synthesis of multicomponent copper-based catalysts for Rochow reaction

Abstract: This work aims to provide a facile, low-cost and scalable method for the preparation of the multicomponent Cu-Cu 2 O-CuO catalysts which are highly interested by the organosilane industry. A series of submicrometer-sized and Cu-based catalysts containing CuO, Cu 2 O and Cu or some of them have been synthesized by a simple low-temperature wet chemical method using CuSO 4 ·5H 2 O as the precursor and N 2 H 4 ·H 2 O as reducing agent. The samples were characterized by X-ray diffraction, thermogravimetric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…The particle with a lattice distance of 2.53 Å corresponded to the 1̅ 11 spacing of CuO. 41 The result fitted well with the XRD result of (CuZn) 3 Al 1 -LDO in Figure 3, indicating the existence of crystalline CuO particles. With the increasing amount of Al in catalysts, as shown in Figure 4b−e, no obvious nanoparticles were detected and all images emerged as typical amorphous structures.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The particle with a lattice distance of 2.53 Å corresponded to the 1̅ 11 spacing of CuO. 41 The result fitted well with the XRD result of (CuZn) 3 Al 1 -LDO in Figure 3, indicating the existence of crystalline CuO particles. With the increasing amount of Al in catalysts, as shown in Figure 4b−e, no obvious nanoparticles were detected and all images emerged as typical amorphous structures.…”
Section: Methodssupporting
confidence: 82%
“…To further ascertain these particles, high-resolution TEM (HRTEM) was performed and is shown in Figure f. The particle with a lattice distance of 2.53 Å corresponded to the 1̅11 spacing of CuO . The result fitted well with the XRD result of (CuZn) 3 Al 1 -LDO in Figure , indicating the existence of crystalline CuO particles.…”
Section: Results and Discussionsupporting
confidence: 55%
“…Of special note is the reported peak at 241.2°C for a mixed CuO-Cu2O-Cu phase by Y. Zhai et al (Zhai et al, 2015), similar to the TPR 2 / TPR 3 peaks located at 242°C / 235°C. The peaks located around 300°C could also be attributed to CuO reduction, as the profile overlap between the reference H2-TPR CuO powder match well with the TPR 2 / TPR 3 profile shape.…”
Section: Temperature-programmed Reduction and Oxidation Of Cuo40_r2supporting
confidence: 52%
“…It has been widely shown that there are synergistic effects among Cu, Cu 2 O, and CuO, as many patents and papers reported that under conventional reaction conditions, neither Cu, Cu 2 O, nor CuO alone achieved satisfactory performance, except for the Cu−Cu 2 O−CuO ternary system . Liu et al reported a kind of ternary‐phase nanoparticles with the optimum weight proportion of 18.1: 53.0: 28.9 (Cu: Cu 2 O: CuO), which achieved 74.5 % of M2 selectivity and 23.4 % of Si conversion .…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%